Market and Company Dimension in the Internet Age - Passaro, Pierluigi (European Scientific Journal, ESJ, 2017)
The analysis and the study of market and company dimension takes on a particular interest for those who analyze and study the set of problems typical of company economy. The starting point, nowadays, is the verification, from most experts openly shown, of the strict correlation of the two phenomena and, actually of their mutual influence. The analysis of these ones assumes a particular attention in light of what is happening in front of our eyes. Those which appeared irrefutable certainties are now completely put into play again, very often, for determined aspects, completely overturned in regard to the previous certainties. Our effort will consist in a detailed study of the two phenomena included in the great world of internet. The company is a very complex organism. It consists of the organization in its inner of a set of functions, which have to be dimensioned one to the others to obtain a mutual functionality and a harmonic development. The organization of the company functions is a binding necessity for adherence of them to the needs and expectations of market to which the company turns its attention and interest. This combination of functions with the chosen external environment represents the focal point of our interest. It is well clear that the changes which intervene either in one or in other environment, that must combine, necessarily produce some variations that assure the lingering of harmony already reached in the two sections.